LncRNA SNHG1 upregulates ROCK2 to reduce cisplatin sensitivity of NSCLC cells by targeting miR-101-3p - Wei, Lei; Yang, Nan; Sun, Lei; Zhang, Lei; Li, Zhongdong; Li, Demin; Qin, Tao; Huang, Hairong (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Cisplatin is the most commonly used chemotherapy drug in clinical settings, and decreased sensitivity or resistance to cisplatin is the main cause of chemotherapy failure or death among cancer patients. Long non-coding RNA (lncRNA) SNHG1 is highly expressed in non-small cell lung cancer (NSCLC) tissues and promotes the proliferation of NSCLC cells, but the effect of SNHG1 on cisplatin sensitivity of NSCLC cells is unclear. Methods: We compared the expression of SNHG1 in cisplatin-sensitive and insensitive NSCLC tissues and explored the molecular mechanism of SNHG1 regulation of the sensitivity of NSCLC cells to cisplatin in vitro. Results: We found that SNHG1 is upregulated in cisplatin insensitive NSCLC tissues and cells, and that it can regulate cisplatin sensitivity of NSCLC cells in vitro. Furthermore, we also found that the expression of miR-101-3p in NSCLC tissues is negatively correlated with SNHG1 or ROCK2. Additionally, in NSCLC cells, SNHG1 and miR-101-3p are mutually suppressed, but miR-101-3p targets the inhibition of ROCK2. More importantly, the regulation of ROCK2 expression in vitro can also change the sensitivity of NSCLC cells to cisplatin. Conclusions: In summary, our results provide novel mechanistic insights into the role of SNHG1/miR-101-3p/ROCK2 signaling in cisplatin resistance of NSCLC cells.